Arp2/3 complex subunit ARPC2 binds to microtubules - Havelková, Lenka; Nanda, Gitanjali; Martinek, Jan; Bellinvia, Erica; Sikorová, Lenka; Šlajcherová, Kateřina; Seifertová, Daniela; Fischer, Lukáš; Fišerová, Jindřiška; Petrášek, Jan; Schwarzerová, Kateřina (Plant science, 2015)
Arp2/3 complex plays a fundamental role in the nucleation of actin filaments (AFs) in yeasts, plants, and animals. In plants, the aberrant shaping and elongation of several types of epidermal cells observed in Arp2/3 complex knockout plant mutants suggest the importance of Arp2/3-mediated actin nucleation for various morphogenetic processes. Here we show that ARPC2, a core Arp2/3 complex subunit, interacts with both actin filaments (AFs) and microtubules (MTs). Plant GFP-ARPC2 expressed in Nicotiana tabacum BY-2 cells, leaf epidermal cells of Nicotiana benthamiana and root epidermal cells of Arabidopsis thaliana decorated MTs. The interaction with MTs was demonstrated by pharmacological approach selectively interfering with either AFs or MTs dynamics as well as by the in vitro co-sedimentation assays. A putative MT-binding domain of tobacco NtARPC2 protein was identified using the co-sedimentation of several truncated NtARPC2 proteins with MTs. Newly identified MT-binding ability of ARPC2 subunit of Arp2/3 complex may represent a new molecular mechanism of AFs and MTs interaction.
Keywords: listy rostlin; mikrofilamenta; Arabidopsis; Actin Cytoskeleton; Plant Roots; rostlinné proteiny; Microtubules; kořeny rostlin; Nicotiana; Actin filaments; Arp2/3; mikrotubuly; Plant Leaves; Actin; Actin-Related Protein 2-3 Complex; tabák; komplex proteinů 2-3 souvisejících s aktinem; Tubulin; Plant Proteins